Pemanfaatan Media Pembelajaran berbasis Teknologi Informasi dalam Meningkatkan Minat Belajar Pendidikan Agama Islam Siswa MTs Muhammadiyah 1 Gondangrejo Karanganyar - Miftahurohman, Miftahurohman; Subando, Joko (Lembaga Yasin AlSys, 2025)
This study aims to describe the utilization of information technology-based instructional media in enhancing students’ interest in learning Islamic Religious Education (PAI) at MTs Muhammadiyah 1 Gondangrejo. A qualitative approach with a case study method was employed, using data collected through observation, interviews, and documentation. Data were analyzed using the interactive model by Miles & Huberman. The findings show that PAI teachers use various technology-based media, such as laptops, flash drives, speakers, LCD projectors, mobile phones, and the internet to deliver content interactively. Lesson preparation includes drafting lesson plans (RPP), checking teaching devices, and providing initial student motivation. The use of ICT media has proven effective in increasing student engagement, motivating learning, and facilitating conceptual understanding, whereas traditional textbook-based learning is less appealing to students. Challenges faced by teachers include limited facilities, technological skills, and varying student comprehension levels. Solutions implemented involve creating learning content, participating in technology training, and adapting media to student needs. These findings align with the theories of Munadi (2013), Arsyad (2017), and Tafonao (2018), which emphasize the importance of appropriate media use in enhancing learning interest and effectiveness.